Impact of a Lactobacillus dominant cervical microbiome, based on 16S-FAST profiling, on the reproductive outcomes of IVF patients - Guan, Wenzheng; Dong, Sitong; Wang, Zhen; Jiao, Jiao; Wang, Xiuxia (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: This study assessed the impact of the cervical microbiome on reproductive outcomes in frozen embryo transfer (FET) patients. Study design: This cross-sectional study included 120 women (aged 20–40 years) undergoing FET. A cervical sample obtained before embryo transfer was analyzed using 16S full-length assembly sequencing technology (16S-FAST), which detects full length 16S rDNA. Results: We found that >48% of the identified Lactobacillus species were novel. The cervical microbiome was clustered into three cervical microbiome types (CMT): CMT1, dominated by L. crispatus; CMT2, dominated by L. iners; and CMT3, dominated by other bacteria. CMT1 had a significantly higher biochemical pregnancy rate (P=0.008) and clinical pregnancy rate (P=0.006) than CMT2 and CMT3. Logistic analysis showed that compared to CMT1, CMT2 and CMT3 were independent risk factors for biochemical pregnancy failure (odds ratio [OR]: 6.315, 95% confidence interval [CI]: 2.047-19.476, P=0.001; OR: 3.635, 95% CI: 1.084-12.189, P=0.037) and clinical pregnancy failure (OR: 4.883, 95% CI: 1.847-12.908, P=0.001; OR: 3.478, 95% CI: 1.221-9.911, P=0.020). A L. crispatus-dominated group as a diagnostic indicator of biochemical and clinical pregnancy positive had area under the curve (AUC) values of 0.651(P=0.008) and 0.645(P=0.007), respectively. Combining the cervical microbiome with embryonic stage optimized the diagnostic performance for biochemical and clinical pregnancy failure with AUC values of 0.743(P<0.001) and 0.702(P<0.001), respectively. Additionally, relative abundance of L. crispatus predicted biochemical pregnancy positive with AUC values of 0.679(P=0.002) and clinical pregnancy positive with AUC values of 0.659(P=0.003). Conclusion: Cervical microbiome profiling using 16S-FAST enables stratification of the chance of becoming pregnant prior to FET. Knowledge of the cervical microbiota may enable couples to make more balanced decisions regarding the timing and continuation of FET treatment cycles.